Types, Strategies, and Functions of Request Speech Acts in Uang Panai Maha(L)R (2016) Movie - Rustan, Megawati; Santosa, Riyadi; Yustanto, Henry; Gusnawaty, Gusnawaty (Journal of Pragmatics Research, 2025)
This study targets a holistic investigation of the types, strategies, and functions carried out by the characters in the 2016 film Uang Panai Maha(R)L and its social context. This study also aims to find the influence of the stages of the film starting from orientation, complication, evaluation, and resolution on the use of types, strategies, and functions of requests carried out by the characters in the film. This study uses a socio-pragmatic approach to investigate speech acts of requests based on Anna Trosborg's theory (1995) to identify types, strategies, and functions in films. This study is supported by using descriptive qualitative research supported by four main stages of analysis by the Santosa (2021) model, combined with Spradley (1980), and Miles and Huberman (1996) starting from domain analysis, taxonomy, components, and cultural themes. The data for this study were taken from dialogues containing the types, strategies, and functions of requests carried out by the characters at each stage of the film. The data source comes from the 2016 film Uang Panai Maha(R)L stages starting from orientation, complication, evaluation, and resolution. The study results indicate that the speech acts of requests uttered by the characters in the film Uang Panai Maha(R)L 2016 tend to fluctuate throughout the stages of the film, namely orientation, complication, evaluation, and resolution.